Hospital healthcare utilizers with medical and psychiatric claims in the Netherlands: a nationwide study - Maarten van Schijndel; Luc Jansen; Jan Busschbach; Jeroen van Waarde; Andre Wierdsma; Henning Tiemeier (BMC, 2022)
Abstract Background Psychiatric and medical multimorbidity is associated with low quality of life, poor functioning and excess mortality. Differences in healthcare utilization between those receiving co-occurring medical and psychiatric healthcare (HUMPCs) and those only receiving medical (HUMCs) or only psychiatric healthcare (HUPCs) may indicate differences in care accessibility, help-seeking behavior and the risk patterns of medical illness. We aimed to assess the occurrence of psychiatric diagnostic groups in HUMPCs compared to HUPCs and to compare their medical and psychiatric claims expenditures. Methods Using Dutch claims data covering psychiatric and medical hospital care in 2010-2011, healthcare utilization differences between HUMPCs and HUPCs were expressed as differences and ratios, accounting for differences in age and sex between groups. Median claims expenditures were then compared between HUMPCs and HUPCs. Results HUMPCs had 40% higher median medical cost of claims compared to HUMCs and a 10% increased number of psychiatric claims compared to HUPCs. HUMPCs were more often diagnosed with: organic disorders; behavioral syndromes associated with physiological disturbances and physical factors; mood [affective] disorders; neurotic, stress related and somatoform disorders; and disorders of adult personality and behavior. By contrast, disorders of psychological development, schizophrenia, schizotypal and delusional disorders, behavioral and emotional disorders with usual onset occurring in childhood, and mental and behavioral disorders due to psychoactive substance abuse were less often diagnosed in this group. Conclusions Both medical and psychiatric disease become more costly where both are present. For HUMPCs the costs of both medical and psychiatric claims for almost all diagnostic groups were higher than for HUPCs and HUMCs.